REGULATORY AND LEGAL SUPPORT OF THE FUNCTIONING OF PUBLIC TRANSPORT AND PROVISION OF TRANSPORT SERVICES TO THE POPULATION OF CITIES IN THE CONDITIONS OF POST-WAR RECONSTRUCTION - Vasylieva, Oleksandra; Veliev, Tymur (Public Administration and Regional Development, 2024)
The article substantiates the need for regulatory support for solving problems with the functioning of public transport, as well as for the provision of transport services in cities of Ukraine in the conditions of post-war reconstruction. It is noted that one of the priority areas of the reconstruction plan is transport infrastructure. It is noted that the peculiarity of urban transport is that it can be in state, communal and private property. Therefore, the difficulty is that the impact on the state and private carrier by local governments is quite limited. It is noted that at the same time, local public authorities have the opportunity to influence transport service providers by concluding or not concluding transactions and determining their terms. It is concluded that regulatory support for the functioning and development of public transport in cities and in general in the settlements of our country requires significant improvement, namely: development and approval electric transport, construction, operation and repair of its facilities, public transport as a whole; defining the principles of interaction of all entities in the field of urban transport, regulations on customers, providers and consumers of transport services, their rights and responsibilities; Determination of priority provisions of public policy in the field of land transport and their implementation (ensuring the safety of transportation, environmental friendliness, inclusivity and availability of passenger transport and its subsequent sustainable development), their coordination with plans and strategies of development of cities and regions, etc.